Quaternary Sediments and Their Relationship to Volcanogenic Massive Sulfide Deposits in the South Banda Basin, Indonesia - Noor C.D Aryanto; H. Kurnio; M.Z Tuakia; A. Tampubolon; B. Pardiarto; B.N Widi; W. Widodo; Kusnawana; Joni Widodo; Yudo Haryadi; et al. (Current Research on Geography, Earth Science and Environment Vol. 1, 2025)
The South Banda back-arc basin is a morphotectonic environment that is part of the South Banda Basin, characterised by a flat morphology with depths ranging from 5000m to 6000m. This region has the potential for the presence of massive sulfide (VMS) deposits, which are associated with and created by volcanic hydrothermal events in submarine environments. The purpose of this study is to analyse and relate morphometric aspects to the Quaternary seabed sediment deposits deposited in an active tectonic basin in the Banda Sea area, including information on the type of sediment and its distribution as well as its relation to volcanic-hosted massive sulfide (VHMS) or VMS mineral deposits. The seabed lithofacies in the Banda Arc area were deposited in several morphotectonic environments. Each morphotectonic environment is distinguished by its distinctive morphological appearance. The types of deposits that are deposited are pelagic and hemipelagic deposits, including turbidite and volcanic origin deposits. Turbidite deposits consist of fine sediments (silt to very fine sand) and coarse sediments (medium sand to gravel). Volcanic deposits consist of gravel, sand, muddy sand, and silt, which are classified as very poorly to moderately well sorted. The grain composition is volcanic lithic, feldspar, augite, hypersthene, and enstatite, which are commonly found in volcanic arcs and troughs. Groups of volcanic grains composed of pyroxene andesite, pumice, and tuffite or siliceous gravel, distributed in the northern and middle parts of the volcanic arc area, are interpreted to originate from the Banda volcanic complex and the Seram-Gorong islands. By connecting seabed sediment characteristics with volcanic and tectonic activity, this study offers valuable indicators for locating potential volcanogenic massive sulfide (VMS) mineral deposits.